The Short-Run Employment Effects of the German Minimum Wage Reform - Marco Caliendo; Alexandra Fedorets; Malte Preuß; Carsten Schröder; Linda Wittbrodt (Institute of Labor Economics (IZA), 2017)
We assess the short-term employment effects of the introduction of a national statutory minimum wage in Germany in 2015. For this purpose, we exploit variation in the regional treatment intensity, assuming that the stronger a minimum wage "bites" into the regional wage distribution, the stronger the regional labour market will be affected. In contrast to previous studies, we draw upon detailed individual wage data from the Structure of Earnings Survey (SES) 2014 and combine it with administrative information on regional employment. Moreover, using the Socio-Economic Panel (SOEP), we are able to affirm the absence of anticipation effects and verify the assumption of a common trend in wages before the reform. Based on hourly wages, we compute two regional bite indicators – the share of affected employees and the Kaitz index – for 141 regional labour markets. In order to get a broader picture, we construct and compare a variety of these measures, including a bite based on full-time workers only. All of these display a considerably strong correlation. Overall, we do not find a pronounced significant effect on regular (full- and part-time) employment in most specifications, although some estimations yield a small significant reduction amounting to 78,000 (roughly 0.3% of all regular jobs). The results concerning marginal employment are more pronounced. We find evidence that mini-jobs dropped substantially from 2014 to 2015, making for a reduction of about 180,000 jobs (about 2.4% of all mini-jobs). This result is robust to a variety of sensitivity tests.
Keywords: J23; J31; J38; 330; minimum wage; regional bite; employment effects